Th1/Th2 cytokine gene polymorphisms in patients with idiopathic pulmonary fibrosis - Vasakova, M; Striz, I; Slavcev, A; Jandova, S; Kolesar, L; Sulc, J (Tissue antigens, 2006)
We investigated 30 patients with idiopathic pulmonary fibrosis (IPF) and 103 healthy volunteers for the cytokines polymorphisms of the IL-1alpha, IL-1beta, IL-1R, IL-1RA, IL-2, IL-4, IL-6, IL-10, IL-12, tumor necrosis factor-alpha, interferon-gamma, transforming growth factor-beta, IL-1beta, IL-2, IL-4, and IL-4RA genes. The strongest correlation of a genotype with the disease was found for gene polymorphisms at the promotor region of IL-4, where the CT genotypes at the positions (-590) and (-33) were more frequent in the IPF group (P < 0.0001, P(corr) < 0.0022; vs P < 0.0001, P(corr) < 0.0022). Our results support the idea of the pathogenic role of cytokine gene polymorphisms in the etiology and pathogenesis of IPF, with emphasize on the IL-4 promotor gene polymorphisms.
Keywords: Adult; senioři; Aged; Male; lidé; Pulmonary Fibrosis; Th2 buňky; lidé středního věku; Humans; Middle Aged; Th2 Cells; Polymorphism, Genetic; Th1 buňky; cytokiny; plicní fibróza; senioři nad 80 let; Cytokines; Aged, 80 and over; mužské pohlaví; polymorfismus genetický; Th1 Cells; dospělí; Case-Control Studies; ženské pohlaví; Female; studie případů a kontrol